Peningkatan Kompetensi Pemuda melalui Pelatihan Pemasangan dan Pemeliharaan Instalasi Listrik Rumah Sederhana - Doni Tri Putra Yanto; Mukhlidi Muskhir; Erita Astrid; Ricky Maulana (Universitas Negeri Padang, 2021)
This study reveals the improvement of community competence, especially youth after participating in the Installation and Maintenance training program for Simple House Installations in Padang City. The competence in question is the ability in the field of installation and maintenance of simple house installations at the household level in the community. The increase in the ability of the training participants is measured using a research instrument in the form of a Performance Assessment Rubric that has gone through a validation process. The research data were analyzed by percentage analysis and interpreted with an improvement table to get the level of improvement achieved. The research subjects were as many as 15 trainees who were representatives of members of the youth organizations of each sub-district in the city of Padang. The results showed that the average participants experienced an increase in the installation and maintenance of simple home electrical installations after participating in training activities where the increase was at a very high level (total average = 83.32). Thus, it can be concluded that the training program held was able to improve the competence of youth youth organizations in the city of Padang in the field of installation and maintenance of simple house installations.